Development of novel benzamide class I selective lysine deacetylase inhibitors as potent anticancer agents - Gill, Jason H.; Sellars, Jonathan D.; Waddell, Paul G.; Shnyder, Steven D.; Grigg, Ronald; Fishwick, Colin W. G. (Journal of enzyme inhibition and medicinal chemistry, 2025)
Small molecule inhibitors of lysine deacetylases (KDACs), exemplified by histone deacetylases (HDACs), exhibit significant promise as cancer therapeutics. Using a modular combinatorial chemistry approach, a novel class of KDAC inhibitors (KDACi) containing the aminophenyl-benzamide headgroup have been developed, which incorporate a vinyl group within the linker region for active site stabilisation and a trifluoromethyl moiety within the capping group to exploit enzyme surface topology. Consequently, a class I selective KDACi ( ) with a preference towards HDAC1 over other class I KDACs was identified. This KDACi orientates differently within the KDAC active site and exhibits an improved antitumour profile relative to the benchmark class I selective KDACi Entinostat ( ). The clinical potential of is further exemplified by the inhibition of tumour growth in an model of ovarian cancer. These results offer significant scope for the rational development of KDACi with improved selectivity against specific KDAC and widespread therapeutic potential.